The Alternative Sigma Factor σ(E) Plays an Important Role in Intestinal Survival and Virulence in Vibrio cholerae - Kovacikova, Gabriela (American Society for Microbiology, 2002)
The alternative sigma factor σ(Ε) (RpoE) is involved in the response to extracytoplasmic stress and plays a role in the virulence of a variety of different bacteria. To assess the role of σ(Ε) in Vibrio cholerae pathogenesis, a ΔrpoE mutant was constructed and analyzed using the infant mouse model. The results here show that σ(Ε) contributes significantly to the virulence of V. cholerae. The ΔrpoE mutant was highly attenuated with a 50% lethal dose more than 3 logs higher than that for the parental strain, and its ability to colonize the intestine was reduced approximately 30-fold. A time course of infection revealed that the number of CFU of the ΔrpoE mutant was approximately 1 log lower than that of the parental strain by 12 h postinoculation and decreased further by 24 h. The defect in virulence in the ΔrpoE mutant thus appears to be a diminished ability to survive within the intestinal environment. The results here also show that σ(Ε) is not required for growth and survival of V. cholerae in vitro at high temperatures but is required under other stressful conditions, such as in the presence of 3% ethanol. As in Escherichia coli, the expression of rpoE in V. cholerae is dependent upon two promoters located upstream of the gene, P1 and P2. P1 appears to be σ(70) dependent, whereas the downstream promoter, P2, is positively autoregulated by σ(Ε).